Tantangan Mewujudkan Sustainable Development Goals (SDGs) Tentang Kesetaraan Gender pada Masyarakat Desa - Mustakimah, Lina; Huriani, Yeni; Zulaeha, Eni (UIN Sunan Gunung Dajti Bandung, 2023)
Abstract: Gender equality is one of the issues that need to be realized globally through the ideas in the Sustainable Development Goals (SDGs). In Indonesia, villages are the smallest level of government structure, having an important role in achieving SDGs at the national level by contributing 74% of national achievements considering that 90% of Indonesia's government areas are villages and 72% of Indonesian people live in villages. Darmaraja Village, Lumbung District, Ciamis Regency is one of the villages that must carry out its development by referring to SGDs achievements, one of which is realizing SDGs no. 5 concerning gender equality in villages. Villages with all their characteristics, uniqueness, and village potential certainly have their challenges in realizing gender equality in the village. This research tries to describe the results of Darmaraja Village's SDGs regarding gender equality and then analyze the obstacles to achieving gender equality in the village. The research results concluded that the SDG's achievement regarding gender equality in Darmaraja Village was still very far from ideal with only a score of 34.91 points. Then the factors that become obstacles are the low level of education of the Darmaraja Village community, patriarchal culture, and misogynistic understanding of women through religious texts.Keywords: Gender Equality, SDGs, Village